VISUAL MOUSE (COLOR TRACKING) - BAHRUDIN, MUHAMMADMUSTAFA (Universiti Teknologi PETRONAS, 2007)
This Final Year Project is about Visual Mouse (Color tracking). This project will demonstrates how a webcam could be used to track objects in front of it and track hand movements to drawon the computer. It is applicable for paper presentations and lectures. This project will deal with algorithm and tools in MATLAB software as its medium. The basic principle of this project would be distinguishing color and use its properties to move a cursor in MATLAB and draw as well.